Effect of Gyttja and Nitrogen Applications on Growth and Flowering of Snapdragons (Antirrhinum majus L.) Plant in the Two Soils Depth - Mjeed, Ardalan J; Ali, Mariwan A. (Kurdistan Journal of Applied Research, 2017)
Plant morphological attribute has been reported to be increased through the application of organic material (Gyttja) to the soil. Snapdragons (Antirrhinum majus L.) was studied under plastic house conditions to determine the effect of two different soil depth-SH (0-20 cm and 20- 40 cm), four different gyttja doses-GD (0, 1, 2, and 3%), and three different nitrogen doses-ND (0, 140, and 280 mg kg-1) on some of the plant’s morphological characters; Plant Height (PH), Fresh Weight Per Plant (FWP), Number of Leaves Per Plant(NLP), Stem Diameter(SD), Number of Branches Per Plant (NBP), Number of Flower Per Spikes (NFPS) and Flower Spike Length (FSL). The results showed that gyttja application at doses of 3%, significantly increased PH, SD, NBP, NFPS, and FSL, while FWP increased only at 2% gyttja application dose and decreased at the 3% dose. The application of 280 mg kg-1 of nitrogen significantly increased (PH, FWP, NLP, NBP, NFPS and FSL). All parameters increased at (0-20 cm) soil depth, and the GD x SH x ND interaction had a significant effect on (SD, NLP, NFPS and FSL). These results suggest that adding of gyttja with nitrogen fertilizer to the calcareous and infertile soil will enhance the morphological attributes of plants.